PERKEMBANGAN PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL DI INDONESIA - Dani, Sapuan (Majalah Keadilan, 2020)
ABSTRACT The purpose of this paper is to find out the development of HAKI protection and law enforcement, which aims to encourage innovation, transfer and dissemination of technology and to gain mutual benefits between producers and users of technology knowledge by creating economic welfare and a balance between rights and obligations. Protection of HKI in Indonesia still needs to be studied in more depth. This writing is a type of normative legal writing. The data used are secondary data consisting of primary, secondary and tertiary legal materials. Data collection was carried out by means of documentation of primary, secondary and tertiary legal materials, as well as interviews with informants which were also conducted and used as a secondary legal material. The data analysis process uses qualitative methods, by analyzing data in the form of documents, regulations, related theories that produce descriptive-analytical data. As a result, the registration of intellectual rights must meet the requirements according to the law which is the recognition and justification of a person's intellectual property rights as evidenced by a registration certificate or by other means of a written registration letter for copyright so that it will obtain legal protection which creates legal certainty.